If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 5x = 40 + -1x Solving 4 + 5x = 40 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4 + 5x + x = 40 + -1x + x Combine like terms: 5x + x = 6x 4 + 6x = 40 + -1x + x Combine like terms: -1x + x = 0 4 + 6x = 40 + 0 4 + 6x = 40 Add '-4' to each side of the equation. 4 + -4 + 6x = 40 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 40 + -4 6x = 40 + -4 Combine like terms: 40 + -4 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| -3/4=-1/2t | | 3(a+8)=39 | | -12=3-2k-2k | | f(x)=6x^2+45x-24 | | 4p-10=-3p+18 | | 1/10p=-3/5 | | 15x-35=70 | | 2/5q=4/7 | | -2/3r=5/8 | | x=14+-8 | | -1/3z=-5/6 | | -m-10m-16=0 | | 3/8r=5/6 | | 1/4z=2/5 | | 2+4=120 | | 2/3q=-15 | | y/(x-1)=2 | | -12x^2=-144 | | 7x+5=-5+2x+30 | | -3x+-35y=14 | | 2w+40+4w=94 | | 1/2q=6 | | 3x^2+8=80 | | 5n+3n=26 | | 35x=15(30-x) | | 4p^2-3=7 | | 3q-32=67 | | 4=2+2f | | 3y-15=15x | | 10=7+3 | | 15a^2b+30ab= | | 3p^2=10 |